Hollow carbon sphere loaded Ni / NiO heterojunction material and preparation method and application thereof

By in situ forming a Ni/NiO heterojunction on the surface of hollow carbon spheres, the problems of slow electron transport of the catalyst and excessive supporting materials were solved, achieving efficient catalyst performance improvement and significantly reducing the dehydrogenation temperature of lithium aluminum hydride.

CN120662356APending Publication Date: 2025-09-19GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510814490.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-18
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

In the existing technology, the electron transmission speed of the catalyst is slow, the catalytic efficiency is low, and the excessive addition of supporting materials leads to reduced atomic utilization, which limits the further improvement of the catalyst.

Method used

Hollow carbon spheres were prepared by a template sacrificial method, and Ni/NiO heterojunctions were formed in situ on their surfaces. SiO2 was used as a template and the template was removed by alkaline etching to prepare hollow carbon sphere-loaded Ni/NiO heterojunction materials.

Benefits of technology

The electron transfer rate and atomic utilization rate of the catalyst were significantly improved, the initial dehydrogenation temperature of lithium aluminum hydride was reduced, and the catalytic efficiency was improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120662356A_ABST
    Figure CN120662356A_ABST
Patent Text Reader

Abstract

The invention discloses a hollow carbon sphere loaded Ni / NiO heterojunction material, which is prepared by the following steps: firstly preparing a solid carbon sphere loaded Ni / NiO heterojunction material SiO2-NC-Ni / NiO by a template sacrifice method, and then removing a SiO2 template by an alkaline etching method to obtain the hollow carbon sphere loaded Ni / NiO heterojunction material NC-Ni / NiO. The preparation method comprises the following steps: 1, preparing PDA coated silicon dioxide solid spheres; 2, preparing PDA coated silicon dioxide solid sphere loaded nickel ions; 3, preparing a carbon-coated silicon dioxide solid sphere loaded nickel-nickel oxide heterojunction; and 4, preparing the hollow carbon sphere loaded nickel-nickel oxide heterojunction. The invention relates to a preparation method of an NC-Ni / NiO doped lithium aluminum hydride hydrogen storage material, which comprises the following steps of: mixing NC-Ni / NiO serving as a catalyst and lithium aluminum hydride under an argon condition, and performing ball milling to obtain LiAlH4-NC-Ni / NiO. When the material is used as a hydrogen storage material, the initial dehydrogenation temperature is 60-70 DEG C, and the hydrogen desorption amount is 7.0-7.2 wt.%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage materials of new energy materials, and in particular to a hollow carbon sphere-loaded Ni / NiO heterojunction material, a preparation method thereof, and applications thereof. Background Art

[0002] Among solid-state hydrogen storage materials, lithium aluminum hydride (LiAlH4) boasts a high hydrogen storage capacity of 10.5 wt.%. However, as a hydrogen storage material, it suffers from poor dehydrogenation kinetics and cycling performance. Currently, the most common solution is to dope transition metal elements or compounds as catalysts. However, this approach suffers from the agglomeration of nanoscale transition metal particles during heating, significantly reducing the number of active sites and thus impacting catalyst performance. Therefore, carbon materials, metal-organic frameworks, or metal compounds are needed as support structures to reduce agglomeration.

[0003] Among them, hollow carbon spheres are used as supporting structures, and the catalytic efficiency and atomic utilization rate can be effectively improved by loading catalyst particles on the surface of hollow carbon spheres. For example, existing literature 1 (Ryu SH, Lee SM, Kim HJ, et al. Concomitant shape and palladium engineering of hollow conjugated microporous photocatalysts to boost visible light-induced hydrogen evolution [J]. Journal of Materials Chemistry A, 2021, 9 (39): 22262-22268.) prepared hollow carbon spheres by a template sacrificial method, and loaded precious metal Pd on the surface of the hollow carbon spheres to achieve the hydrogen evolution performance increased to 7100 μmol·h -1 g -1 However, the material's utilization rate of visible light with a wavelength of 500nm or more is extremely low, and the catalyst's conversion efficiency of photons in this region is only 0.46%.

[0004] The reason is that although this technical solution can utilize the large specific surface area of ​​the hollow structure to improve the atomic utilization rate of Pd, since its preparation method is a simple reduction method to reduce Pd to the carrier surface, when loaded Pd, Pd and hollow carbon spheres cannot form a heterojunction, resulting in slow electron transmission speed and narrow band gap width inside the metal active sites, and ultimately leading to extremely low absorption efficiency of visible light with a wavelength of more than 500nm, which in turn affects the hydrogen evolution rate.

[0005] In order to improve the utilization rate of the catalyst in the visible light region of more than 500nm in wavelength, a heterojunction can be formed between a noble metal and a supporting material, so as to accelerate electron transfer speed and increase band gap width to improve the utilization efficiency of long wavelength light. The method for forming a transition metal heterojunction on the surface of a supporting structure is currently realized, and a transition metal is loaded on the supporting material and then heat-treated, so that the grain boundary is reset, forming a heterojunction. For example, existing document 2 (Zhang GR, Liu J X, Wei S, et al. Thermally induced in situ fabrication of TiO2 / CNheterojunction dopant for enhancement of hydrogen storage properties ofLiAlH4[J]. Journal of Materials Science & Technology, 2024, 203: 227-236.) is used as C3N4 supporting material, TiO2 is loaded on the outer surface, and, by using C3N4 and TiO2 a method for jointly heat-treating, it is realized that TiO2 / CN heterojunction is prepared in situ on C3N4. The heterojunction obtained by this technical solution effectively increases the electron transfer rate between the catalyst and LiAlH4, promotes the breaking of the Al-H bond, and ultimately reduces the initial hydrogen desorption temperature to 76°C. However, in this technical solution, the amount of C3N4 introduced as a catalyst reaches 70% of the total mass of the catalyst, while the TiO2 that actually plays a catalytic role only accounts for 30% of the catalyst, that is, there is a problem of excessive addition of supporting material. This results in the catalyst having an extremely low atomic utilization rate, which in turn limits its technical problem of further improving the catalytic efficiency.

[0006] In order to improve the atomic utilization rate of the catalyst, the inventors of the present invention used a support material with better effect and less addition in their previous work. Specifically, existing document 3 (Xiang Cuili, Yang Zexuan, Zou Yongjin, Xu Fen, Sun Lixian. A composite material of GO and Ni-TiO2 loaded simultaneously and its preparation method and application) uses GO as the support material, on which MIL-125 and Ni-MOF are grown in situ, and finally the catalyst Ni-TiO2-GO is obtained by calcination. This technical solution reduces the initial dehydrogenation temperature of MgH2 to 182°C, and the hydrogen release amount is 3.82wt.%. In this technical solution, the content ratio of the support material GO and its load Ni-TiO2 is only 1:2, that is, the support material GO only accounts for 33% of the catalyst, thereby effectively improving the atomic utilization rate of the catalyst, thereby greatly improving the catalytic efficiency of the catalyst. However, in this technical solution, due to the preparation method of first growing the MOFs material in situ and then heat-treating it, a heterojunction cannot be formed inside the catalyst, which leads to the inability to effectively increase the electron transfer rate, thereby limiting the further improvement of its catalytic efficiency.

[0007] From the above analysis, it can be seen that the existing technology has the following problems:

[0008] 1. Among the catalysts used for lithium aluminum hydride, the catalyst with an internal heterojunction has a faster internal electron transmission speed and a higher catalytic efficiency. The introduction of lithium aluminum hydride can effectively reduce the initial dehydrogenation temperature of lithium aluminum hydride;

[0009] 2. If the proportion of supporting materials in the catalyst is too high, the atomic utilization rate of the catalyst will be reduced, thereby limiting the catalytic efficiency of the catalyst. Summary of the Invention

[0010] The present invention is a hollow carbon sphere-loaded Ni / NiO heterojunction material and its preparation method and application. The present invention addresses the technical problems existing in the prior art by utilizing a template sacrificial method to form a heterojunction through in-situ loading, thereby increasing the internal electron transfer rate of the lithium aluminum hydride catalyst. Specifically,

[0011] 1. Using SiO2 as a template, hollow carbon spheres were prepared as support materials through a template sacrificial method;

[0012] 2. Ni is adsorbed in situ on the support material and a Ni / NiO heterojunction is prepared in situ on the support material by heat treatment.

[0013] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0014] A hollow carbon sphere-loaded Ni / NiO heterojunction material is prepared by first preparing a solid carbon sphere-loaded Ni / NiO heterojunction material SiO2-NC-Ni / NiO through a template sacrificial method, and then removing the SiO2 template through an alkaline etching method to obtain a hollow carbon sphere-loaded Ni / NiO heterojunction material, referred to as NC-Ni / NiO.

[0015] The microstructure of the hollow carbon sphere-loaded Ni / NiO heterojunction material is a hollow spherical structure with a size of 300 nm; the Ni / NiO heterojunction material is uniformly distributed on the surface of the hollow carbon sphere in the form of small particles.

[0016] A method for preparing a hollow carbon sphere-supported Ni / NiO heterojunction material comprises the following steps:

[0017] Step 1, preparation of PDA-coated silica solid spheres, first, ammonia water, anhydrous ethanol, and deionized water are mixed and stirred in a stirring manner to obtain solution A, then, ethyl silicate is placed in solution A and stirred to obtain solution B, finally, dopamine hydrochloride aqueous solution is added to solution B and stirred to obtain solution C, after mixing, solution C is allowed to stand, and after standing, the obtained product is centrifuged, washed, and dried to obtain PDA-coated silica solid spheres, referred to as SiO2-PDA;

[0018] In step 1, the volume ratio of ammonia water, ethyl silicate, dopamine hydrochloride aqueous solution, anhydrous ethanol, and deionized water is 1:1:16:24:80;

[0019] In step 1, the stirring conditions are: a rotation speed of 40-60 rpm / min and a stirring temperature of 20-30°C;

[0020] The stirring time of solution A is 20-30 min;

[0021] The stirring time of solution B is 10-15 min;

[0022] The stirring time of solution C is 5-10 min;

[0023] The duration of the standing process of solution C is 30-60 min;

[0024] Step 2, preparation of PDA-coated silica solid spheres loaded with nickel ions, first, placing the SiO2-PDA obtained in step 1 in deionized water under stirring and then ultrasonication to obtain solution D, then placing nickel nitrate hexahydrate in solution D with stirring, and after the stirring is completed, centrifuging and drying the obtained product to obtain PDA-coated silica solid spheres loaded with nickel, referred to as SiO2-PDA-Ni;

[0025] The mass ratio of the nickel element in the nickel nitrate hexahydrate in step 2 to the carbon element in the dopamine hydrochloride in step 1 is 6:1;

[0026] In step 2, the ultrasonic dispersion time of solution D is 10-20 min, and after nickel nitrate hexahydrate is added to solution D, the stirring speed is 40-60 rpm / min, the stirring temperature is 20-30° C., and the stirring time is 18-24 h;

[0027] Step 3, preparation of carbon-coated silica solid sphere loaded nickel-nickel oxide heterojunction, calcining under argon conditions, the SiO2-PDA-Ni obtained in step 2 is calcined to obtain carbon-coated silica solid sphere loaded nickel-nickel oxide heterojunction, abbreviated as SiO2-NC-Ni / NiO.

[0028] In step 3, the calcination conditions are as follows: a heating rate of 2-5°C / min, a calcination temperature of 800°C, a calcination time of 2-3h, and an argon atmosphere;

[0029] Step 4, preparation of hollow carbon sphere-supported nickel-nickel oxide heterojunction, first, under the conditions of stirring and then ultrasonication, the SiO2-NC-Ni / NiO obtained in step 3 is placed in a sodium hydroxide solution to obtain solution E, and then solution E is reacted in a water bath. After the water bath is completed, the obtained product is centrifuged, washed and dried to obtain a hollow carbon sphere-supported nickel-nickel oxide heterojunction, referred to as NC-Ni / NiO;

[0030] In step 4, the concentration of the sodium hydroxide solution is 0.5 mol L -1 ;

[0031] In step 4, the water bath time of solution E is 12-16 hours, and the water bath temperature is 30-40°C.

[0032] A method for preparing an NC-Ni / NiO-doped lithium aluminum hydride hydrogen storage material comprises the following steps: using NC-Ni / NiO as a catalyst, mixing the catalyst and lithium aluminum hydride, and ball milling the mixture under argon gas to obtain a lithium aluminum hydride hydrogen storage material based on NC-Ni / NiO, referred to as LiAlH4-NC-Ni / NiO; the amount of NC-Ni / NiO added to the LiAlH4-NC-Ni / NiO accounts for 7 wt.% of the total mass; and ball milling conditions under argon gas, a ball-to-material ratio of 200:1, a ball milling speed of 400-450 rpm, and a ball milling time of 55-65 min.

[0033] When the obtained LiAlH4-NC-Ni / NiO is used as a hydrogen storage material, the initial dehydrogenation temperature is 60-70°C and the hydrogen release amount is 7.0-7.2wt.%.

[0034] The technical effects of the present invention have been tested and the specific contents are as follows:

[0035] XRD detection of the present invention shows that: NC-Ni / NiO contains characteristic peaks of shaped carbon, Ni and NiO;

[0036] The present invention is tested by SEM and found that the microscopic morphology of NC-Ni / NiO is spherical with a diameter of 200-300nm, a rough surface, and a hollow structure in the sphere, i.e., a hollow spherical structure;

[0037] TEM detection of the present invention shows that: a hollow spherical structure of NC-Ni / NiO can be observed. At the same time, it can be determined through lattice fringes that the lattice spacing of 0.205 nm corresponds to the (111) crystal plane of Ni, and the lattice spacing of 0.241 nm corresponds to the (003) crystal plane of NiO. In addition, there is a clear phase interface between the two crystal planes, indicating the existence of a heterojunction.

[0038] The dehydrogenation test of the present invention shows that: using NC-Ni / NiO as a catalyst, the added amount of the catalyst is 7 wt.%, the initial dehydrogenation temperature is 60-70° C., and the dehydrogenation amount is 7.0-7.2 wt.%.

[0039] Therefore, the present invention has the following advantages over the prior art:

[0040] 1. The hollow carbon sphere-loaded Ni / NiO heterojunction material prepared by the present invention improves the atomic utilization of the catalyst and enhances the catalytic efficiency of the catalyst;

[0041] 2. The Ni / NiO heterojunction prepared by the present invention can accelerate the electron transfer rate inside the catalyst and improve the catalytic efficiency of the catalyst;

[0042] 3. The hollow carbon sphere-loaded Ni / NiO heterojunction material prepared in the present invention is used as a catalyst to introduce lithium aluminum hydride to prepare a lithium aluminum hydride hydrogen storage material based on NC-Ni / NiO, abbreviated as LiAlH4-NC-Ni / NiO, which significantly reduces the initial dehydrogenation temperature to 60-70°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 XRD patterns of SiO2-PDA, SiO2-PDA-Ni, SiO2-NC-Ni / NiO, and NC-Ni / NiO prepared in Example 1;

[0044] Figure 2 The XRD pattern of the uncoated SiO2 prepared in Example 1;

[0045] Figure 3This is a field emission scan of the PDA-coated silica solid sphere prepared in Example 1;

[0046] Figure 4 This is a field emission scan of the SiO2-PDA-Ni prepared in Example 1;

[0047] Figure 5 This is a field emission scanning image of SiO2-NC-Ni / NiO prepared in Example 1;

[0048] Figure 6 This is a field emission scanning image of NC-Ni / NiO prepared in Example 1;

[0049] Figure 7 TEM image of NC-Ni / NiO prepared in Example 1;

[0050] Figure 8 Lattice diffraction fringes of NC-Ni / NiO prepared in Example 1;

[0051] Figure 9 Dehydrogenation curve of LiAlH4-NC-Ni / NiO prepared in Example 1;

[0052] Figure 10 XRD pattern of NC prepared in Comparative Example 1;

[0053] Figure 11 This is a field emission scan of the NC prepared in Comparative Example 1;

[0054] Figure 12 Dehydrogenation curves of LiAlH4-Ni-NC, LiAlH4-NiO-NC and LiAlH4-Ni-NiO-NC prepared in Comparative Examples 1, 2 and 3. DETAILED DESCRIPTION

[0055] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0056] Example 1

[0057] A method for preparing a hollow carbon sphere-supported Ni / NiO heterojunction material comprises the following steps:

[0058] Step 1, preparation of PDA-coated silica solid spheres, first, 2 mL of ammonia water, 48 mL of anhydrous ethanol, and 160 mL of deionized water were mixed and stirred for 30 min to obtain solution A, then, 2 mL of ethyl silicate was placed in solution A and stirred for 15 min to obtain solution B, finally, 16 mL of 0.265 M dopamine hydrochloride aqueous solution was added to solution B and stirred for 10 min to obtain solution C, after mixing, solution C was allowed to stand for 1 h, and after standing, the obtained product was centrifuged, washed, and dried to obtain PDA-coated silica solid spheres, referred to as SiO2-PDA.

[0059] In order to prove the composition of SiO2-PDA, XRD test was carried out. At the same time, for comparison, a material without adding PDA, namely SiO2, was prepared and XRD test was carried out.

[0060] The test results of SiO2-PDA are as follows Figure 1 As shown in the figure, only the characteristic peaks of PDA are present, and the characteristic peaks of silicon dioxide are absent. The test results show that SiO2 is completely coated with PDA.

[0061] The test results of SiO2 are as follows Figure 2 As shown, there are characteristic peaks of SiO2;

[0062] The test results show that a core composed of SiO2 can be obtained by hydrolyzing the ethyl silicate in step 1.

[0063] In order to prove the microstructure of SiO2-PDA, SEM test was carried out, and the test results are as follows Figure 3 As shown in FIG, the microstructure of SiO2-PDA is a solid sphere with a diameter of 300 nm and a smooth surface.

[0064] Step 2, preparation of PDA-coated silica solid spheres loaded with nickel ions, first, under stirring and then ultrasonic conditions, 1g of SiO2-PDA obtained in step 1 is placed in 400mL of deionized water to obtain solution D, then, under stirring time of 24h, 11.6316g of nickel nitrate hexahydrate is placed in solution D and stirred, after the stirring is completed, the obtained product is centrifuged, washed and dried to obtain PDA-coated silica solid spheres loaded with nickel, referred to as SiO2-PDA-Ni;

[0065] In step 2, the conditions for stirring first and then ultrasonicating are: stirring time is 10 minutes, and ultrasonicating time is 10 minutes.

[0066] In order to prove the composition of SiO2-PDA-Ni, XRD test was carried out. The test results are as follows Figure 1As shown in the figure, SiO2-PDA-Ni has the characteristic peak of fixed carbon, but no characteristic peak of Ni element. The test results show that Ni is adsorbed on the surface of SiO2-PDA in the form of ions.

[0067] In order to prove the microstructure of SiO2-PDA-Ni, SEM test was carried out. The test results are as follows Figure 4 As shown, SiO2 / PDA-Ni 2+ The microstructure of the SiO2-PDA still remains a solid sphere with a diameter of 300 nm, but the surface is rough. Compared with step 1, it can be seen that Ni is successfully loaded on the SiO2-PDA surface through step 2, resulting in a rough surface.

[0068] Step 3, preparation of carbon-coated silica solid sphere-loaded nickel-nickel oxide heterojunction, under argon conditions, at a heating rate of 2°C / min, a calcination temperature of 800°C, and a calcination time of 2h, the SiO2-PDA-Ni obtained in step 2 is calcined to obtain a carbon-coated silica solid sphere-loaded nickel-nickel oxide heterojunction, referred to as SiO2-NC-Ni / NiO.

[0069] In order to prove the composition of SiO2-NC-Ni / NiO, XRD test was carried out. The test results are as follows Figure 1 As shown in the figure, in addition to the characteristic peaks of shaped carbon, SiO2-NC-Ni / NiO also has the characteristic peaks of Ni and NiO.

[0070] In order to verify the microstructure of SiO2-NC-Ni / NiO, SEM test was carried out. The test results are shown in the figure below. Figure 5 As shown, the microstructure of SiO2-NC-Ni / NiO has no substantial difference from that in step 2, that is, it still maintains a solid sphere with a diameter of 300 nm and a rough surface.

[0071] Step 4, preparation of hollow carbon sphere-loaded nickel-nickel oxide heterojunction, first, the SiO2-NC-Ni / NiO obtained in step 3 is placed in 400 mL of 0.5 M sodium hydroxide solution under stirring and then ultrasonication to obtain solution E, then, solution E is reacted in a water bath at a water bath temperature of 30°C and a water bath time of 16 h. After the water bath is completed, the obtained product is centrifuged, washed and dried to obtain a hollow carbon sphere-loaded nickel-nickel oxide heterojunction, referred to as NC-Ni / NiO.

[0072] In step 4, the conditions for stirring first and then ultrasonicating are: stirring time is 10 minutes, and ultrasonicating time is 10 minutes.

[0073] In order to prove the composition of NC-Ni / NiO, XRD test was carried out. The test results are as follows Figure 1As shown in Figure 3, NC-Ni / NiO contains the characteristic peaks of shaped carbon, Ni and NiO.

[0074] In order to verify the microstructure of NC-Ni / NiO, SEM test was carried out. The test results are as follows Figure 6 As shown, the microstructure of NC-Ni / NiO still maintains a spherical shape with a diameter of 300nm and a rough surface, but the spherical structure is hollow, i.e., a hollow spherical structure. Compared with step 2, it can be seen that step 3 successfully etches SiO2-NC-Ni / NiO.

[0075] In order to further prove the hollow structure of NC-Ni / NiO and prove that NC-Ni / NiO has a heterojunction, TEM test was carried out. The test results are as follows Figure 7 and Figure 8 As shown, the hollow spherical structure of NC-Ni / NiO; at the same time, it can be determined through the lattice fringes that the lattice spacing of 0.205nm corresponds to the (111) crystal plane of Ni, and the lattice spacing of 0.241nm corresponds to the (003) crystal plane of NiO, and there is an obvious phase interface between the two crystal planes, indicating the existence of a heterojunction.

[0076] To demonstrate the role of NC-Ni / NiO as a catalyst for lithium aluminum hydride hydrogen storage materials, a lithium aluminum hydride hydrogen storage material based on NC-Ni / NiO was prepared. The hydrogen storage material was prepared by ball milling under argon conditions using NC-Ni / NiO as a catalyst at a catalyst dosage of 7 wt.%, a catalyst to lithium aluminum hydride ball-to-ball ratio of 200:1, a ball milling speed of 400 rpm, and a ball milling time of 60 minutes to obtain the NC-Ni / NiO-based lithium aluminum hydride hydrogen storage material, referred to as LiAlH4-NC-Ni / NiO.

[0077] In order to prove the catalytic performance of NC-Ni / NiO, a dehydrogenation performance test was conducted. The specific method of the dehydrogenation performance test is to increase the temperature to 300°C at a heating rate of 3°C / min. At the same time, for comparison, the dehydrogenation performance test was conducted on pure lithium aluminum hydride. The dehydrogenation performance test results are shown in the figure below. Figure 9 As shown,

[0078] The initial hydrogen desorption temperature of LiAlH4 is 133.6℃, ​​and the amount of hydrogen desorption is 7.5wt.%;

[0079] The initial hydrogen desorption temperature of LiAlH4-NC-Ni / NiO is 66.6℃, and the hydrogen desorption amount is 7.2wt.%.

[0080] The test results show that using NC-Ni / NiO as a catalyst can significantly reduce the initial dehydrogenation temperature by 70°C.

[0081] In order to demonstrate the role of each component in NC-Ni / NiO in the technical scheme and the preparation method of in-situ loading, that is, the influence of Ni / NiO heterojunction on performance, comparative examples 1, 2 and 3 are provided, in which hollow carbon spheres NC are loaded with Ni and NiO separately, and loaded with Ni and NiO simultaneously. Among them, for the purpose of comparison and ease of expression, a reference example, the preparation method of hollow carbon spheres NC, is provided.

[0082] Reference ratio

[0083] A method for preparing hollow carbon spheres NC, wherein the steps not specifically described are the same as those in Example 1, except that step 2 is not required, and the material obtained in step 4 is hollow carbon spheres NC, referred to as NC for short.

[0084] In order to prove the composition of NC, XRD test was carried out. The test results are as follows Figure 10 As shown in Figure 3, NC only contains obvious characteristic peaks of shaped carbon C, indicating that carbon spheres were successfully prepared.

[0085] In order to verify the microstructure of NC, SEM test was carried out. The test results are shown in Figure 11 As shown, the NC microstructure remains spherical with a diameter of 300 nm, a relatively smooth surface, and a hollow structure, i.e., a hollow spherical structure. Compared with the NC-Ni / NiO in Example 1, the basic microstructure is essentially the same, but the NC surface becomes rough due to the loading of Ni / NiO on the NC surface.

[0086] Comparative Example 1

[0087] A method for preparing NC-Ni with non-in situ nickel loading on hollow carbon spheres is disclosed. Based on the hollow carbon spheres NC obtained in the reference example, 0.003 g of NC and 0.018 g of nickel powder are mixed with the same mass ratio of carbon source to nickel source as in Example 1, specifically, PDA and nickel nitrate hexahydrate are added in a ratio of 1:6. The obtained material is named NC-Ni, and the lithium aluminum hydride hydrogen storage material based on NC-Ni is further named LiAlH4-NC-Ni.

[0088] The dehydrogenation performance test results of LiAlH4-NC-Ni are as follows Figure 12 As shown, the initial dehydrogenation temperature is 98.5°C and the dehydrogenation amount is 7.0 wt.%. Comparison of the test results with the LiAlH4-NC-Ni / NiO obtained in Example 1 shows that the NC-Ni / NiO prepared by the in situ preparation method can significantly reduce the initial dehydrogenation temperature from 98.5°C to 66.6°C, a decrease of 31.9°C, although it can only slightly increase the dehydrogenation amount from 7.0 wt.% to 7.2 wt.%.

[0089] Comparative Example 2

[0090] A method for preparing NC-NiO, a hollow carbon sphere non-in situ loaded with nickel oxide, is disclosed. Based on the hollow carbon sphere NC obtained in the reference example, 0.003 g of NC and 0.018 g of nickel oxide powder are mixed with the same mass ratio of carbon source to nickel source as in Example 1, specifically, PDA and nickel nitrate hexahydrate are added in a ratio of 1:6. The obtained material is named NC-NiO, and the lithium aluminum hydride hydrogen storage material based on NC-Ni is further named LiAlH4-NC-NiO.

[0091] The dehydrogenation performance test results of LiAlH4-NC-NiO are as follows Figure 12 As shown, the initial dehydrogenation temperature is 96.4°C and the dehydrogenation amount is 6.8wt.%. Comparing the test results with the LiAlH4-NC-Ni / NiO obtained in Example 1, it can be seen that when the NC-Ni / NiO obtained by the in situ preparation method is used as a catalyst, the dehydrogenation amount is slightly increased from 6.8wt.% to 7.2wt.%, but the initial dehydrogenation temperature can be significantly reduced by 29.8°C.

[0092] Comparative Example 3

[0093] A method for preparing NC-NiO, a hollow carbon sphere non-in situ loaded with nickel oxide, is disclosed. Based on the hollow carbon sphere NC obtained in the reference example, 0.003 g of NC, 0.009 g of nickel powder, and 0.009 g of nickel oxide powder are mixed with the same mass ratio of carbon source to nickel source as in Example 1, specifically, PDA and nickel nitrate hexahydrate are added in a ratio of 1:6. The obtained material is named NC-Ni-NiO, and the obtained lithium aluminum hydride hydrogen storage material based on NC-Ni is named LiAlH4-NC-Ni-NiO.

[0094] The dehydrogenation performance test results of LiAlH4-NC-Ni-NiO are as follows Figure 12 As shown, the initial dehydrogenation temperature is 99.7°C and the dehydrogenation amount is 7.1 wt.%. Comparing the test results with the LiAlH4-NC-Ni / NiO obtained in Example 1, it can be seen that when the NC-Ni / NiO obtained by the in situ preparation method is used as a catalyst, the dehydrogenation amount is slightly increased from 7.1 wt.% to 7.2 wt.%, but the initial dehydrogenation temperature can be significantly reduced by 33.1°C.

[0095] The following conclusions can be drawn from the above examples and comparative examples: By analyzing Example 1 and Comparative Examples 1, 2, and 3, it can be seen that the Ni / NiO heterojunction improves the catalytic efficiency of the catalyst by accelerating the electron transfer within the catalyst, thereby significantly reducing the initial dehydrogenation temperature of LiAlH4, but does not significantly improve the hydrogen release amount of LiAlH4.

Claims

1. A hollow carbon sphere-supported Ni / NiO heterojunction material, characterized in that: Through the template sacrificial method, the solid carbon ball loaded Ni / NiO heterojunction material SiO2-NC-Ni / NiO was first prepared, and then the SiO2 template was removed by alkaline etching to obtain the hollow carbon ball loaded Ni / NiO heterojunction material, referred to as NC-Ni / NiO.

2. The hollow carbon sphere-supported Ni / NiO heterojunction material according to claim 1, characterized in that: The microstructure of the hollow carbon sphere-loaded Ni / NiO heterojunction material is a hollow spherical structure with a size of 300 nm; the Ni / NiO heterojunction material is uniformly distributed on the surface of the hollow carbon sphere in the form of small particles.

3. A method for preparing a hollow carbon sphere-loaded Ni / NiO heterojunction material, characterized in that The following steps are involved: Step 1, preparation of PDA-coated silica solid spheres, first, ammonia water, anhydrous ethanol, and deionized water are mixed and stirred in a stirring manner to obtain solution A, then, ethyl silicate is placed in solution A and stirred to obtain solution B, finally, dopamine hydrochloride aqueous solution is added to solution B and stirred to obtain solution C, after mixing, solution C is allowed to stand, and after standing, the obtained product is centrifuged, washed, and dried to obtain PDA-coated silica solid spheres, referred to as SiO2-PDA; Step 2, preparation of PDA-coated silica solid spheres loaded with nickel ions, first, placing the SiO2-PDA obtained in step 1 in deionized water under stirring and then ultrasonication to obtain solution D, then placing nickel nitrate hexahydrate in solution D with stirring, and after the stirring is completed, centrifuging and drying the obtained product to obtain PDA-coated silica solid spheres loaded with nickel, referred to as SiO2-PDA-Ni; Step 3, preparation of carbon-coated silica solid sphere-loaded nickel-nickel oxide heterojunction, calcining the SiO2-PDA-Ni obtained in step 2 under argon conditions to obtain carbon-coated silica solid sphere-loaded nickel-nickel oxide heterojunction, referred to as SiO2-NC-Ni / NiO; Step 4, preparation of hollow carbon sphere-loaded nickel-nickel oxide heterojunction, first, under the conditions of stirring and then ultrasonication, the SiO2-NC-Ni / NiO obtained in step 3 is placed in a sodium hydroxide solution to obtain solution E, and then solution E is reacted in a water bath. After the water bath is completed, the obtained product is centrifuged, washed and dried to obtain a hollow carbon sphere-loaded nickel-nickel oxide heterojunction, abbreviated as NC-Ni / NiO.

4. The preparation method according to claim 3, wherein: In step 1, the volume ratio of ammonia water, ethyl silicate, dopamine hydrochloride aqueous solution, anhydrous ethanol, and deionized water is 1:1:16:24:80; The mass ratio of the nickel element in the nickel nitrate hexahydrate in step 2 to the carbon element in the dopamine hydrochloride in step 1 is 6:1; In step 4, the concentration of the sodium hydroxide solution is 0.5 mol L -1 .

5. The preparation method according to claim 3, wherein: In step 1, the stirring conditions are: a rotation speed of 40-60 rpm / min and a stirring temperature of 20-30°C; The stirring time of solution A is 20-30 min; The stirring time of solution B is 10-15 min; The stirring time of solution C is 5-10 min; The duration of the standing process of solution C is 30-60 minutes.

6. The preparation method according to claim 3, wherein: In step 2, the ultrasonic dispersion time of solution D is 10-20 min, and after nickel nitrate hexahydrate is added to solution D, the stirring speed is 40-60 rpm / min, the stirring temperature is 20-30° C., and the stirring time is 18-24 h; In step 3, the calcination conditions are as follows: a heating rate of 2-5°C / min, a calcination temperature of 800°C, a calcination time of 2-3h, and an argon atmosphere; In step 4, the water bath time of solution E is 12-16 hours, and the water bath temperature is 30-40°C.

7. A method for preparing NC-Ni / NiO doped lithium aluminum hydride hydrogen storage material, characterized in that The following steps are involved: Under argon conditions, NC-Ni / NiO is used as a catalyst, and the catalyst and lithium aluminum hydride are mixed and ball-milled to obtain a lithium aluminum hydride hydrogen storage material based on NC-Ni / NiO, which is abbreviated as LiAlH4-NC-Ni / NiO.

8. The preparation method according to claim 76, wherein: In the LiAlH4-NC-Ni / NiO, the addition amount of NC-Ni / NiO accounts for 7 wt.% of the total mass.

9. The preparation method according to claim 7, characterized in that: The ball milling conditions are as follows: under argon gas, a ball-to-material ratio of 200:1, a ball milling speed of 400-450 r / min, and a ball milling time of 55-65 min.

10. The preparation method according to claim 7, characterized in that: When the obtained LiAlH4-NC-Ni / NiO is used as a hydrogen storage material, the initial dehydrogenation temperature is 60-70°C and the hydrogen release amount is 7.0-7.2wt.%.

Citation Information

Cited By

  • Hollow spherical titanium-nickel oxide heterojunction and preparation method and application thereof

    CN122538130A